Development and Evaluation of a Digital Intervention for Fulfilling the Needs of Older Migrant Patients With Cancer: User-Centered Design Approach - Sungur, Hande (J Med Internet Res, 2020)
BACKGROUND: Older migrant patients with cancer face many language- and culture-related barriers to patient participation during medical consultations. To bridge these barriers, an eHealth tool called Health Communicator was developed in the Netherlands. Essentially used as a digital translator that can collect medical history information from patients, the Health Communicator did not include an oncological module so far, despite the fact that the prevalence of Dutch migrant patients with cancer is rising. OBJECTIVE: This study aims to systematically develop, implement, and conduct a pilot evaluation of an oncological module that can be integrated into the Health Communicator to stimulate patient participation among older Turkish-Dutch and Moroccan-Dutch patients with cancer. METHODS: The Spiral Technology Action Research model, which incorporates 5 cycles that engage key stakeholders in intervention development, was used as a framework. The listen phase consisted of a needs assessment. The plan phase consisted of developing the content of the oncological module, namely the question prompt lists (QPLs) and scripts for patient education videos. On the basis of pretests in the do phase, 6 audiovisual QPLs on patient rights, treatment, psychosocial support, lifestyle and access to health care services, patient preferences, and clinical trials were created. Additionally, 5 patient education videos were created about patient rights, psychosocial support, clinical trials, and patient-professional communication. In the study phase, the oncological module was pilot-tested among 27 older Turkish-Dutch and Moroccan-Dutch patients with cancer during their consultations. In the act phase, the oncological model was disseminated to practice. RESULTS: The patient rights QPL was chosen most often during the pilot testing in the study phase. Patients and health care professionals perceived the QPLs as easy to understand and useful. There was a negative correlation between the tool’s ease of use and patient age. Patients reported that using the module impacted the consultations positively and thought they were more active compared with previous consultations. Health care professionals also found patients to be more active than usual. Health care professionals asked significantly more questions than patients during consultations. Patients requested to see the patients’ rights video most often. Patients rated the videos as easy to understand, useful, and informative. Most of the patients wanted to use the tool in the future. CONCLUSIONS: Older migrant patients with cancer, survivors, and health care professionals found the oncological module to be a useful tool and have shown intentions to incorporate it into future consultation sessions. Both QPLs and videos were evaluated positively, the latter indicating that the use of narratives to inform older, low-literate migrant patients with cancer about health-related topics in their mother tongue is a viable approach to increase the effectiveness of health care communication with this target group.